The Mass Media and Media Literacy in Mexico - Pérez Viveros, Marlen Yadari; Campos Guido, Laura Lizeth (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This research analyzes the media environment in Mexico, under an adverse context: reporters who work for public media must submit to the control of the government in turn, international accusations are constant for the lack of freedom and security, and the media are losing credibility in the face of an avalanche of information that spreads on social networks that differs from what they spread. In its investigations to determine the Media Development Indicators, UNESCO reveals the situation that the press is going through in the country, and the adversities that reporters face to carry out their work.